(untitled) (Международный научный журнал «Инженер», 2026)
This article reviews modern innovative technologies for generating electricity from waste. Converting waste into energy is one of the most effective, innovative and economically viable approaches to achieving environmental sustainability today. Also, the introduction of waste-to-energy technology is not only a solution to environmental problems, but also a new development factor for the country’s economy. Effective methods are analyzed based on international experience and their environmental and economic advantages are studied. The application of technologies is analyzed using the example of advanced projects from leading countries in the world.